Effective corporate governance mechanisms, ownership structure and financial reporting quality: evidence from Oman / Muneer Rajab Amrah and Mohammed Mahdi Obaid. - Amrah, Muneer Rajab; Obaid, Mohammed Mahdi (Universiti Teknologi MARA Shah Alam and Accounting Research Institute (ARI), 2019)
This study aimed to examine the relationship between corporate governance effectiveness and financial reporting quality among family and non-family owned companies in the Sultanate of Oman. This study used a panel dataset for 68 companies listed on the Muscat Securities Market for 6 years from 2013 to 2018. The study contributes to the literature by extending previous financial reporting quality with a consideration of the Sultanate of Oman business environment where family ownership control is more common. Additionally, this study contributes by using a composite measure of corporate governance mechanisms to capture the combined effect of corporate governance effectiveness on the propensity of financial reporting quality, based on the agency's theoretical framework. This study is based on the difference between family and non-family owned firms with Type I and Type II agency problems, with differences in ownership and control. This study contributes to the literature by examining the influences of corporate governance effectiveness on financial reporting quality, which is expected to be different between family and non-family firms. The empirical results indicate that the association between corporate governance effectiveness and its financial reporting quality is positive and significant for both, the full sample as well as the non-family firms. However, this relationship appears to be weaker for family owned firms.